Differential calculus : made easy! - Comandante, Jr., Felipe L. (Mandaluyong City, Philippines : National Book Store, 2005)
The author's major objective throughout the writing of this textbook-workbook is to present the differential calculus to engineering, computer science, and mathematics majors in a simple and understandable language.- - Preface
1. Relations and functions -- 2. Limits and continuity of algebraic functions -- 3. The derivative -- 4. Maxima and minima involving algebraic functions -- 5. Exponential and logarithmic functions -- 6. Trigonometric and inverse trigonometric functions -- 7. Hyperbolic and inverse hyperbolic functions -- 8. Parametric equations, curvature, and indeterminate forms -- 9. Functions of several variables.
Keywords: CALCULUS